Pemenuhan Hak atas Informasi Konsumen terhadap Penggunaan Produk Kemasan Makanan dan Minuman Gelas Berbahan Kertas yang Mengandung Mikroplastik di Kota Yogyakarta - Adiba Mutiara Mona; Bagya Agung Prabowo (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research aims to determine the fulfillment of consumers rights to information regarding the use of paper cup food and beverage packaging products containing microplastics in Yogyakarta City and to determine the responsibilities of business actors regarding the fulfillment of consumers rights to information regarding the use of paper cup food and beverage packaging products containing microplastics in Yogyakarta City. Paper cup packaging is in great demand by business actors because it is practical and environmentally friendly, but in reality paper cup packaging products contain microplastics that are harmful to health. This type of research is a normative juridical method using the statute approach and conceptual approach. The results of this research indicate that the fulfillment of consumers rights to information regarding paper cup food and beverage packaging products containing microplastics in Yogyakarta City has been guaranteed in Law Number 8 of 1999 concerning Consumer Protection, but in reality business actors still do not provide information regarding the use and long-term harmful impacts on health of paper cup packaging products. Business actors responsibility to include information correctly, clearly, and honestly on paper cup packaging products has not been fulfilled. Consumers feel disadvantaged by business actors because they do not include information on paper cup food and beverage packaging products containing microplastics, which can result in health risks.